Hypofractionated partial breast irradiation after breast-conserving surgery for patients with early stage breast cancer in China Mainland: a single-arm prospective trial - Xiaomeng Zhang; Xiaofang Wang; Zhuohua Xu; Yajuan Chu; Xingxing Chen; Li Zhang; Jin Meng; Wei Shi; Zhaozhi Yang; Xin Mei; Xiaoli Yu; Zhen Zhang; et al. (Scientific Reports)
Abstract To report the results of a single-arm, prospective partial breast irradiation (PBI) trial from China mainland using a dose of 40.05 Gy in 15 fractions delivered with intensity-modulated radiation therapy (IMRT) technique for patients with early stage breast cancer. Patients aged ≥ 50 years who underwent breast-conserving surgery for unifocal non-lobular invasive breast cancer, with pathological T1 disease, clear margins, negative axillary nodes, and positive hormonal receptors, were recruited. The primary endpoint was 3-year cosmetic deterioration, and secondary endpoints included adverse events, ipsilateral breast tumor recurrence (IBTR), regional recurrence, and survivals. This trial is registered with ClinicalTrials.gov (registration No. NCT03411174). From Jan of 2015 to July of 2018, 208 out of 222 patients recruited were evaluable and included in final analysis. The median follow-up was 66.3 (range: 42.0-105.4) months. The 3-year overall cosmetic deterioration rate was 3.5%. The rates of grade 2 radiation dermatitis and breast induration was 5.8% and 1.5%, respectively. No one experienced ≥ grade 2 breast pain, edema, or telangiectasia. The 5-year cumulative incidence of IBTR and RR was 0.5%. No one developed DM. The 5-year DFS was 99.0%. Four patients died from non-breast cancer causes, and the 5- year OS was 97.9%. In conclusion, we observed lower rates of cosmetic deterioration, IBTR, and ≥ grade 2 acute/late normal tissue effects following PBI with a moderately hypofractionated regimen delivered with IMRT technique. Therefore, this regimen represents an attractive option when an external beam PBI approach is chosen to treat a patient with low-risk early breast cancer.